Isoliquiritigenin and liquiritin from Glycyrrhiza uralensis inhibit α-synuclein amyloid formation. Issue 89 (13th September 2016) - Liao, Mingyan; Zhao, Yudan; Huang, Lizi; Cheng, Biao; Huang, Kun
Abstract : Bioactive isoliquiritigenin and liquiritin inhibit α-synuclein aggregation and extend the life span of the C. elegans model of Parkinson's disease. Abstract : Parkinson's disease (PD), with widespread aggregation of α-synuclein in the form of Lewy bodies as a neuropathological hallmark, is a rising threat for ageing society. Glycyrrhiza uralensis is an herbal medicine and sweets used for centuries in Asia and Europe, its major pharmacologically active ingredients include isoliquiritigenin (ILG), liquiritin (LT), liquiritigenin (LG) and glycyrrhizic acid (GA). Here, we investigated the effects of Glycyrrhiza uralensis ethanol extract (GUE) and the above four compounds, on the aggregation of α-synuclein in vitro and in a transgenic Caenorhabditis elegans PD model NL5901. In vitro, ILG, LT and GUE inhibit the amyloid formation of α-synuclein and alleviate the toxicity caused by aggregates; moreover, ILG could disaggregate preformed fibrils. In vivo, ILG, LT and GUE not only reduce amyloid formation in C. elegans NL5901, but also extend its life span. Together, these data suggest that ILG and LT may be further considered as candidates for PD treatment.